Low coherency of wind induced seismic noise: implications for gravitational wave detection. (3rd November 2022) - Satari, Hamid; Blair, Carl; Ju, Li; Blair, David; Zhao, Chunnong; Saygin, Erdinc; Meyers, Patrick; Lumley, David
Abstract: Seismic noise poses challenges for gravitational wave detection. Effective vibration isolation and methods to subtract unshieldable Newtonian noise (NN) are examples. Seismic arrays offer one way to deal with these issues by making use of correlations between seismic ground measurements and noise inside the detector. In this paper we find that wind induced seismic noise is incoherent and our results show that it can dramatically reduce the projected low frequency sensitivity of future gravitational wave detectors. To quantify this, we measure the coherence length of wind induced seismic noise from 0.06–20 Hz in three distinct locations: close to a building, among tall trees and in shrubs. We show that wind induced seismic noise is ubiquitous and reduces the coherence lengths from several hundred meters to 2–40 m for 0.06–0.1 Hz, from > 60 m to 3–16 m for 1.5–2.5 Hz and from > 35 m to 1–16 m around 16.6 Hz in the study area. This leads to significant loss of velocity resolution of the array for primary microseism and 5 times worse NN cancellation by Wiener filtering at 2 Hz, while it may not pose additional limitation to NN cancellation between 10–20 Hz.